ANALISIS PESAN DAKWAH ISLAM DALAM KOMUNIKASI TRADISIONAL KATOBA PADA MASYARAKAT MUNA - Hadirman Hadirman; Ardianto Ardianto; Musafar Musafar (Potret Pemikiran, 2019)
The purpose of this article is to describe  at the text of the katoba tradition as a medium for Islamic propaganda in the Muna community. The tradition of katoba as a traditional communication medium that is believed to be effective in conveying Islamic values to the child being tested. The purpose of this study is to describe the forms of Islamic da'wah messages in the katoba tradition to the Muna community. The method used in this research is descriptive-qualitative. Based on the results and language, it appears that one of the katoba traditions in the Muna community is one of which functions as an Islamic transmission messages of Islamic da’wah. The messages of Islamic da'wah in the katoba tradition are packaged in ritual language related to fundamental values in Islam, namely the creed, prayer, fasting, pilgrimage, and zakat. Keywords: Da'wah Message, Katoba Tradition, Muna Community. Tujuan artikel ini adalah mendeksripsikan bentuk-bentuk pesan dakwah Islam dalam komunikasi tradisional katoba pada masyarakat Muna. Tradisi katoba sebagai media komunikasi tradisional yang diyakini efektif  dalam menyampaikan pesan-pesan dakwah Islam pada anak yang di-katoba berdasarkan agama yang diyakininya orang tua seorang anak. Metode penelitian yang dipergunakan untuk mengumpulkan data adalah deskriptif-kualitatif. Berdasakan hasil dan pembahasan tampak bahwa komunikasi tradisional katoba pada masyarakat Muna salah satunya berfungsi sebagai transmisi pesan dakwah Islam. Pesan-pesan dakwah Islam  dalam dalam komunikasi tradisional katoba berkaitan dengan sahadha ’syahadat’, sambahea ‘salat’, poasa ’puasa’, hadhi ‘haji’, dan zakati ‘zakat’.  Kata kunci: Pesan Dakwah; Tradisi Katoba; Masyarakat Muna.